Advances in design engineering : proceedings of the XXIX International Conference INGEGRAF, 20-21 June 2019, Logroño, Spain /: proceedings of the XXIX International Conference INGEGRAF, 20-21 June 2019, Logroño, Spain. ([2020]) - Unknown
No abstract available